2014
DOI: 10.1016/j.resp.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory perception measured by cortical neural activations in individuals with generalized anxiety disorder

Abstract: There has been evidence for the effect of anxiety on the neural processing of respiratory sensation using the respiratory-related evoked potentials (RREP) elicited by inspiratory occlusions. This study tested the RREP elicited by inspiratory occlusions in a group of outpatients with generalized anxiety disorder (GAD) and a group of healthy controls. We hypothesized that the RREP P3 peak would be modulated in the GAD patients. A RREP oddball paradigm of 150-ms inspiratory occlusion protocol was used in 15 GAD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
(54 reference statements)
3
21
0
Order By: Relevance
“…The RREP method was previously described in a few comparable studies ( Chan and Davenport, 2010b ; Chan et al, 2014 ). In the current study, the electroencephalography (EEG) was sampled from cortical sites C3 and C4 at 1 kHz with a 40-channel EEG system (NuAmps, Compumedics Neuroscan Inc., Charlotte, NC, USA), bandpass filtered from DC to 50 Hz and referenced to the bilateral mastoids.…”
Section: Methodsmentioning
confidence: 99%
“…The RREP method was previously described in a few comparable studies ( Chan and Davenport, 2010b ; Chan et al, 2014 ). In the current study, the electroencephalography (EEG) was sampled from cortical sites C3 and C4 at 1 kHz with a 40-channel EEG system (NuAmps, Compumedics Neuroscan Inc., Charlotte, NC, USA), bandpass filtered from DC to 50 Hz and referenced to the bilateral mastoids.…”
Section: Methodsmentioning
confidence: 99%
“…Previous neuroimaging studies demonstrated that negative affectivity might also impact the neural processing of respiratory sensations (Chan et al, 2015;Chan, von Leupoldt, Bradley, Lang, & Davenport, 2012;Chan, von Leupoldt, Liu, & Hsu, 2014;Chenivesse et al, 2014;von Leupoldt, Chan, Esser, & Davenport, 2013). It has been suggested that this impact is mediated by (para)limbic brain areas such as insular cortex, anterior cingulate cortex (ACC), and amygdala (Davenport & Vovk, 2009;Evans, 2010;Herigstad, Hayen, Wiech, & Pattinson, 2011;Paulus, 2013;Scano et al, 2013;von Leupoldt et al, 2008;von Leupoldt & Dahme, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These cortical dipole recordings of cerebral neuronal activations during the processing of information from respiratory muscle afferents are identified with the short- and long-latency peaks of Nf, P1, N1, P2, and P3 (Chan and Davenport, 2010 ). The short-latency exogenous (i.e., being affected majorly by the external factors such as stimulus intensity and airway resistance) peaks of Nf and P1 were found related to respiratory stimulus discrimination (Knafelc and Davenport, 1999 ; Davenport et al, 2012 ), while the long-latency endogenous (i.e., being affected majorly by the internal factors such as focused attention and emotion) peaks of P2 and P3 were found related to the affective dimension of respiratory perception (von Leupoldt et al, 2010b ; Chan et al, 2014 ). The N1 peak is thought to reflect both exogenous and endogenous aspects as it was found affected by manipulating physiological factors (Chou and Davenport, 2007 ; Davenport et al, 2007 ), but also by manipulating psychological factors (Harver et al, 1995 ; Webster and Colrain, 2000 ).…”
Section: Introductionmentioning
confidence: 99%